2019
DOI: 10.30848/pjb2019-3(5)
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiological responses of guar [Cyamopsis tetragonoloba (L.) Taub.] to multiple stresses of drought, heat and salinity

Abstract: Plant responses to abiotic stresses such as drought, salt, and heat, have been studied separately, but in fact, plants are exposed simultaneously to a combination of stresses. Therefore, the objective of this study was to explore the morphophysiological responses of the guar plant to the combination of heat, drought, and salinity with respect to that to an individual stress. Five treatments including heat, drought, salinity, a combination of multiple stresses and control were applied to two guar accessions nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The high temperature inside the leaves results in a decrease in stomatal conductance in olives and this decrease in stomatal conductance aims to minimize the risk of xylem embolism. Similar to the study on Cyamopsis tetragonoloba with a high temperature of 42 °C, the stomatal conductance value was reduced to 45 mmol m -2 s -1 , lower than the control of 49 µmol CO2 m -2 s -1 (Alshameri et al, 2019). At high temperatures, low water availability and high evapotranspiration favor a decrease in stomatal conductance because a higher transpiration rate results in lower xylem vessel pressure (Haworth et al, 2018).…”
Section: Resultssupporting
confidence: 75%
“…The high temperature inside the leaves results in a decrease in stomatal conductance in olives and this decrease in stomatal conductance aims to minimize the risk of xylem embolism. Similar to the study on Cyamopsis tetragonoloba with a high temperature of 42 °C, the stomatal conductance value was reduced to 45 mmol m -2 s -1 , lower than the control of 49 µmol CO2 m -2 s -1 (Alshameri et al, 2019). At high temperatures, low water availability and high evapotranspiration favor a decrease in stomatal conductance because a higher transpiration rate results in lower xylem vessel pressure (Haworth et al, 2018).…”
Section: Resultssupporting
confidence: 75%
“…Another drought-tolerant guar variety, BWP-5595, also demonstrated increased expression levels of three genes of the SWEET (Sugars Will Eventually Be Exported Transporter) family of sugar transporters [27,72]. This fact is also in line with the proposed concept.…”
Section: Mechanisms Behind the Guar Drought Tolerance 231 Effects Of ...supporting
confidence: 75%
“…Thereby, the number of pods per plant was most negatively affected by drought, whereas the number of seeds per pod appeared to be the least responsive trait [15,24]. The experiments of Alshameri and co-workers [27] accomplished in Pakistan showed that the drought-induced decrease in the number of pods formed was accompanied by a drop in the number of leaves, leaf area, leaf dry weight, total shoot biomass and plant height.…”
Section: Genotypic Variability Of Guar In Respect Of Drought Tolerancementioning
confidence: 98%
“…In a salinity study, irrigation with saline water with EC iw of 9 dS m −1 resulted in an average reduction in yield by 63% compared to the control (Suthar et al., 2018). The comparison of seed germination and seedling growth also revealed diverse salinity responses of genotypes (Rasheed et al., 2015; Suthar et al., 2019). The salt tolerance index (STI) for shoot biomass, representing the performance ratio under salinity to control, was 1.35 and 1.58 for salt‐tolerant genotypes and 0.21 and 0.20 for salt‐sensitive genotypes (Sandhu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%